REPRODUKSI KEKUASAAN DAN IDEOLOGI KEAGAMAAN DALAM FILM TUHAN, IZINKAN AKU BERDOSA : ANALISIS WACANA KRITIS - Nanda Tri Wardana Pasaribu; Fiza Anjani; Stevani Mahdalena Naibaho; Hera Chairunisa (Jurnal Bastra (Bahasa dan Sastra), 2025)
Film is a powerful medium in shaping, maintaining, or challenging social and ideological structures. Tuhan, Izinkan Aku Berdosa (2024), directed by Hanung Bramantyo, adapts the controversial novel Tuhan, Izinkan Aku Menjadi Pelacur! by Muhidin Dahlan, critically examining the reproduction of power and religious ideology. This study analyzes how religious ideology and power structures are represented and reinforced through narratives, dialogue, and visual elements. Using Critical Discourse Analysis (CDA) by Teun A. van Dijk, the research focuses on social context, particularly how power dynamics and religious ideology shape societal structures and individual agency. Adopting a qualitative descriptive approach, data were collected through documentation techniques, including dialogue transcription, visual analysis, and contextual interpretation. Findings indicate that religious ideology functions as a tool of social control, where religious leaders, such as Abu Darda, maintain dominance and suppress dissent. The protagonist, Kiran, initially conforms to religious norms but faces injustices—sexual violence, betrayal, and abuse—that push her to challenge religious structures. Her choice to enter prostitution is not mere moral decline but an act of resistance against religious hypocrisy and power reproduction. This study concludes that film effectively constructs and critiques dominant ideological narratives, highlighting the intersection of gender, power, and religious discourse while illustrating the stigmatization and oppression of those who deviate from religious norms. These findings contribute to media and cultural studies by emphasizing how religious ideology in film reinforces or critiques power structures in society. by emphasizing how religious ideology in film can either reinforce or critique power structures in society.